Endoscopic ultrasonography-guided deployment of embolization coils and cyanoacrylate injection in gastric varices versus coiling alone: a randomized trial - Robles-Medranda, Carlos; Oleas, Roberto; Valero, Manuel; Puga-Tejada, Miguel; Baquerizo-Burgos, Jorge; Ospina, Jesenia; Pitanga-Lukashok, Hannah (Endoscopy, 2020)
Background Gastric variceal bleeding is a life-threating condition with challenging management. We aimed to compare the efficacy and safety of endoscopic ultrasonography (EUS)-guided coil embolization and cyanoacrylate injection versus EUS-guided coil embolization alone in the management of gastric varices. Methods A single-center, parallel-randomized controlled trial involving 60 participants with gastric varices (GOV II and IGV I) who were randomly allocated to EUS-guided coil embolization and cyanoacrylate injection (n = 30) or EUS-guided coil embolization alone (n = 30). The primary end points were the technical and clinical success rates of both procedures. The secondary end points were the reappearance of gastric varices during follow-up, along with rebleeding, the need for reintervention, and complication and survival rates.Results The technical success rate was 100 % in both groups. Immediate disappearance of varices was observed in 86.7 % of patients treated with coils and cyanoacrylate, versus 13.3 % of patients treated with coils alone (P < 0.001). Median survival time was 16.4 months with coils and cyanoacrylate versus 14.2 months with coils alone (P = 0.90). Rebleeding occurred in 3.3 % of patients treated with combined treatment and 20 % of those treated with coils alone (P = 0.04). With combined treatment, 83.3 % of patients were free from reintervention versus 60 % with coils alone (hazard ratio 0.27; 95 % confidence interval 0.095 – 0.797; P = 0.01).Conclusions EUS-guided coil embolization with cyanoacrylate injection achieved excellent clinical success, with lower rates of rebleeding and reintervention than coil treatment alone. Multicenter studies are required to define the most appropriate technique for gastric variceal obliteration.